2022
DOI: 10.1001/jamapediatrics.2022.3079
|View full text |Cite|
|
Sign up to set email alerts
|

Utility of the Ages and Stages Questionnaire to Identify Developmental Delay in Children Aged 12 to 60 Months

Abstract: ImportanceThe Ages and Stages Questionnaire (ASQ) is a commonly used developmental screening tool, but its utility is debated.ObjectivesTo conduct a a systematic review and meta-analysis to evaluate ASQ’s utility as a screening or diagnostic tool to identify developmental delay in children aged 12-60 months.Data SourcesMedline, EMBASE, CINAHL, PsycINFO, and Mednar were searched from inception until December 2021.Study SelectionStudies meeting both criteria were included. ASQ was performed at age 12 to 60 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 86 publications
1
15
0
Order By: Relevance
“…One prospective study considered the ASQ-3 equivalent to the Bayley-III at 2 years of CA to detect moderate to severe neurodevelopmental impairment [ 24 ]. A recent meta-analysis including 36 studies concluded that the ASQ-3 performance to identify developmental delay in children aged between 12 and 60 months was moderate, with a pooled sensitivity of 0.77 (95% CI, 0.64–0.86), a pooled specificity of 0.81 (95% CI, 0.75–0.86), a pooled positive likelihood ratio of 4.10 (95% CI, 3.17–5.30), and a pooled negative likelihood ratio of 0.28 (95% CI, 0.18–0.44) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…One prospective study considered the ASQ-3 equivalent to the Bayley-III at 2 years of CA to detect moderate to severe neurodevelopmental impairment [ 24 ]. A recent meta-analysis including 36 studies concluded that the ASQ-3 performance to identify developmental delay in children aged between 12 and 60 months was moderate, with a pooled sensitivity of 0.77 (95% CI, 0.64–0.86), a pooled specificity of 0.81 (95% CI, 0.75–0.86), a pooled positive likelihood ratio of 4.10 (95% CI, 3.17–5.30), and a pooled negative likelihood ratio of 0.28 (95% CI, 0.18–0.44) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each domain score places a participant in a category: (1) low risk, (2) monitor (scores 1 or more and less than 2 SDs from the mean), and (3) refer (scores more than 2 SDs from the mean) . The ASQ-3 has demonstrated good psychometric properties . The 10- and 18-month ASQ-3 assessments have a 30-day before and after validity window, for example, the 18-month assessment may be administered to a child from age 17 months and 0 days to 18 months and 30 days.…”
Section: Methodsmentioning
confidence: 99%
“…Similar null results on the ASQ-3 among infants with prenatal exposure to maternal SARS-CoV-2 infection have been reported from other geographical regions, including Kuwait and China; however, it should be noted that both the COMBO Initiative and other research groups have found slightly lower parent-reported developmental scores in infants born during the pandemic compared with those born before the pandemic. To date, the cumulative available data have relied on parent-reported measures such as the ASQ-3, which has only moderate sensitivity and specificity for estimating actual neurodevelopmental delays . Furthermore, parent-reported measures of infant development might be at greater risk of biased perception during a global pandemic due to parental stress and reduced parental exposure to other children and typical infant developmental trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the cumulative available data have relied on parent-reported measures such as the ASQ-3, which has only moderate sensitivity and specificity for estimating actual neurodevelopmental delays. 21 Furthermore, parent-reported measures of infant development might be at greater risk of biased perception during a global pandemic due to parental stress and reduced parental exposure to other children and typical infant developmental trajectories. It is therefore important to use standardized observational measures to assess associations between maternal SARS-CoV-2 infection status during pregnancy and neurodevelopmental outcomes.…”
Section: Introductionmentioning
confidence: 99%